Determination of Multiple Antioxidant Activities of Endemic Tricholoma anatolicum H.H Doğan & Intini Collected from Turkey - Hatıra Taşkın; Tülin Eker; Fuat Bozok; Hasan Hüseyin Doğan; Saadet Büyükalaca (Turkish Journal of Agriculture: Food Science and Technology)
Tricholoma anatolicum H.H. Doğan & Intini is known as the most prized mushroom species in Feke region of Turkey. This mushroom species is collected from Cedar (Cedrus libani) forests and therefore is named as Cedar mushroom in this region. It is collected and consumed by local collectors and also exported to Far East countries such as Japan by exporting companies. Therefore, it is important to investigate the nutritional and medical importance of this species. The aim of this study is to reveal the antioxidant activity of methanol extract in different concentrations (1, 2 and 4 mg/mL) of T. anatolicum H.H. Doğan & Intini collected from Feke district of Adana province of Turkey in 2015. In this study, it was determined that total phenolic content of this mushroom was 56 mg/kg. 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO) and reducing power (RP) activities given in trolox (µM) and ferric-reducing antioxidant power (FRAP) given in FeSO4 (µM) were found as 449, 180, 337 and 2 at the highest concentration (4 mg/mL), respectively. As a result, it could be suggested that methanol extract of T. anatolicum H.H. Doğan & Intini has significantly antioxidant activity.